Calciphylaxis: A successful outcome whilst on peritoneal dialysis - Ana Gaspar; Luis Falcão; Sofia Correia; Maria João Carvalho; Anabela Rodrigues; Antonio Cabrita (RDPLF, 2019)
Calciphylaxis is a life threatening disease for which patients with chronic kidney disease, particular those on dialysis, are at increased risk. As it is a rare condition, treatment options are limited and duration of treatment is not clear, especially when it comes to patients on renal replacement treatment with peritoneal dialysis. We report a case of a 55 year-old woman with end stage renal disease on renal replacement treatment with peritoneal dialysis for five months that presented with severe calciphylaxis of both legs. She had started haemodialysis at the age of 31 and 3 later she received a cadaveric renal transplant that lasted for 20 years. She was treated with warfarin due to atrial fibrillation diagnosis. The treatment approach was multimodal and multidisciplinary and included treatment with sodium thiosulfate and hyperbaric oxygen, warfarin suspension and maintenance of optimized peritoneal dialysis prescription. Additionally, wound dressings were done every other day and antibiotics started whenever there were signs of infection and pain was managed with high doses of opiates and pain adjuvants. There was significant improvement and the patient kept peritoneal dialysis treatment with preserved residual renal function. This raises the question, if there is a need to transition calciphylaxis patients on peritoneal dialysis to haemodialysis, as it is possible to ensure a high efficiency dialysis program with automated peritoneal dialysis.